2019
DOI: 10.1021/acs.jpcc.9b00207
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Photoluminescence and Energy-Transfer Dynamics in Mn2+-Doped (C4H9NH3)2PbBr4 Two-Dimensional (2D) Layered Perovskite

Abstract: Reported here are the low-temperature photoluminescence (PL), energy-transfer mechanism, and exciton dynamics of Mn 2+ -doped two-dimensional (2D) perovskites that show interesting differences from their three-dimensionally doped counterpart. Dopant emission in 2D system shows increased PL intensity and shortened lifetime with increase of temperature and strong dopant emission even at low temperatures. Transient absorption (TA) spectroscopy reveals the dominant role of "hot" excitons in dictating the fast ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 41 publications
5
63
1
Order By: Relevance
“…Such results further confirm that the emission of Mn in hybrid metal halides is strongly coupled with the excitons.T oexhibit an intense red emission from the Mn dopants,t he photoluminescence of the host (that is,e xcitonic emission) should also be intense.I nterestingly,av ery low amount of dopants (less than 0.030 %) are sufficient to obtain high PLQYs.Such enhanced exciton-dopant exchange coupling interactions is probably due to high quantum confinement as excitons can diffuse in only one dimension. [33] Thee xact nature of exciton-dopant coupling for hybrid metal halides remains unclear. Some authors reported that energy transfer is occurring only between free excitons and Mn because the self-trapped exciton states are indirect transient states with unpopulated ground states that could block electron exchange in Dexter energy transfer.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations
“…Such results further confirm that the emission of Mn in hybrid metal halides is strongly coupled with the excitons.T oexhibit an intense red emission from the Mn dopants,t he photoluminescence of the host (that is,e xcitonic emission) should also be intense.I nterestingly,av ery low amount of dopants (less than 0.030 %) are sufficient to obtain high PLQYs.Such enhanced exciton-dopant exchange coupling interactions is probably due to high quantum confinement as excitons can diffuse in only one dimension. [33] Thee xact nature of exciton-dopant coupling for hybrid metal halides remains unclear. Some authors reported that energy transfer is occurring only between free excitons and Mn because the self-trapped exciton states are indirect transient states with unpopulated ground states that could block electron exchange in Dexter energy transfer.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[37] Thus,t ou nravel the mechanism of luminescence in our Mn doped lead halide, temperature-dependent PL measurements were performed for (TDMP)PbBr 4 (Supporting Information, Figure S10) and (TDMP)PbBr 4 :Mn (Figure 3a,b). [33] At low temperature (below ca. 120 K), only one emission band originating from self-trapped excitons can be observed for both doped and undoped materials.Athigher temperatures (above ca.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…The thermally activated exciton and its energy transfer to the Mn 2+ ions can be responsible for the enhanced emission intensity when the temperature was in the range of 363‐423 K (as shown in the inset of Figure C). From previous reports, one knows that the exciton could be easily activated at elevated temperature, and then it transferred the energy to the Mn 2+ ions, resulting in the increased emission intensity. Most noticeably of all, the emission intensity at 423 K maintained around 64.5% of its initial value at 303 K which means that the Mn 2+ ‐activated Cs 3 Cu 2 I 5 halides exhibited strong resistance to the temperature.…”
Section: Resultsmentioning
confidence: 99%